Expansive Measures Versus Lyapunov Exponents - Armijo-Averill, A (American Mathematical Society, 2018)
In this paper we investigate the relation between measure-expan-siveness and hyperbolicity. We prove that non-atomic invariant ergodic measures with all of their Lyapunov exponents positive are positively measure-expansive. We also prove that local diffeomorphisms robustly positively measure-expansive are expanding. Finally, we prove that a C1-volume-preserving diffeomorphism that cannot be accumulated by positively measure-expansive diffeomorphisms has a dominated splitting. © 2018 American Mathematical Society.